Educação inclusiva: Análise e intervenção em uma sala de recursos - De Oliveira, Marileide Antunes; Leite, Lúcia Pereira [UNESP] (FapUNIFESP (SciELO), 2011)
This paper is based on the Support Paradigm, which establishes the principles to the inclusive education, which indicates educational adjustments participating in the regular school to all students. This study aimed to analyze a special classroom working arrangements and to describe an intervention implemented having a special classroom teacher as participant. Data collection comprised the following phases: (a) special classroom description; (b) analysis of the teacher's teaching plan; (c) application of survey and discussion comprising theory and practice on inclusive education; (d) curricular adaptation fulfilling. Data analysis comprised: special classroom characterization, survey analysis, comparative analysis of curricular adaptation. As results, the study shows divergences between public educational policies and school reality. The intervention provided the teacher with a reflection about her on-work performance based on new teaching procedures.
Inclusive education: Analysis and intervention in a special classroom
Keywords: Curriculum; Educational objectives; Educational psychology; Inclusive education; Special education